The utilisation of gluten fractions as quality parameters in selected South African wheat cultivars - Wentzel, Barend Smit (University of the Free State, 2010)
The association between hexaploid wheat (Triticum aestivum L.) quality parameters and gluten protein were determined for selected South African wheat cultivars. Reversed-phase high-performance liquid chromatography (RP-HPLC) and size-exclusion HPLC (SE-HPLC) were used to separate protein fractions. The influence of the environment was much higher for RPHPLC fractions than for SE-HPLC fractions, and genotype contributed much more to the expression of SE-HPLC. Correlations between yield, kernel characteristics and milling properties were low for both chromatography procedures. Bread making properties showed significant correlations with HPLC fractions. RP-HPLC gluten fraction showed the best correlation with alveograph strength and loaf volume. Polymeric proteins showed the highest correlation with mixograph development time, alveograph extensibility, tenacity and configuration of the curve. This confirms the effect of gluten on dough strength and extensibility. Narrow sense heritability indicated that large polymeric proteins could be considered for indirect selection of alveograph and mixograph parameters.
Dissertation (M.Sc. (Plant Sciences: Plant Breeding))--University of the Free State, 2010
Keywords: Wheat -- Quality -- South Africa; Gluten; Dough strength; Dough extensibility; SE-HPLC; RP-HPLC